Práticas arquivísticas em autarquias de fiscalização profissional: pré-diagnóstico dos Conselhos Federais - Meissane Andressa da Costa Leão (2021)
Survey conducted through a records survey questionnaire, applied to the 29 Federal Councils of regulated Professions, which comprise a set of approximately 580 bodies of the indirect public administration in Brazil. Some of these Councils have been active for more than 50 years however, only in 2019, an instrument was created to classify the documents of the main activities, approved by the National Archives. Absence of information was noted about how these entities were dealing with their archival documents or accumulating them. The research aimed to collect data about national and institutional archival public policies, public information policy, existence of archivists in Supervisory Boards and Permanent Document Evaluation Committee (CPAD), structure of the file in the organization charts, deletions of documents; among other preliminary data on the record management these municipalities, which make the federal executive branch. Through the 2013 legal Opinion of the Ministry of Justice / Federal Attorney General (AGU), the body clarified that it is responsibility of the National Archives to guide these Councils on document management. In the literature review, 27 terms were found for “archival diagnosis” and there is no clarity or consensus on its object, meaning and methodology. A literature review of the diagnoses produced in 1950 about the documents of the federal executive branch, until 2017, with the Diagnosis produced by Record Management System (SIGA) was made. Based on the diagnostic chapter, a questionnaire was prepared with questions about the treatment of the record, which was sent by the e-Sic information access systems on the 29 Federal Councils websites. 14 results were received and analyzed. It has been shown that most Councils: do not apply the management tools of the National Archives; it has not been invited to SIGA meetings,it does not guide its regionals in the treaty with documentation ;it does not have the unit or sector status in the organization charts; it does not have archival repositories; or even computerized systems with Computerized Electronic Records Management Systems (ERMS) requirements, being only a Electronic Document Management system (GED); it does not have a safeguard plan, among other notes.